The psychic envelopes in psychoanalytic theories of infancy - Mellier, Denis (Frontiers in Psychology, 2014)
This paper aims to review the topic of psychic envelopes and to sketch the main outlines of this concept in infancy. We first explore the origins of the concept in Freud's 'protective shield' and then its development in adult psychoanalysis before going on to see how this fits in infancy with post-Bionian psychoanalysis and development. Four central notions guide this review: 1) Freud's “protective shield” describes a barrier to protect the psychic apparatus against potentially overflowing trauma. It is a core notion which highlights a serious clinical challenge for patients for whom the shield is damaged or faulty: the risk of confusion of borders between the internal/external world, conscious/unconscious, mind/body, or self-conservation/sexuality. 2) Anzieu's “Skin-Ego” is defined by the different senses of the body. The different layers of experienced sensation, of this body-ego, go on to form the psychic envelope. This theory contributes to our understanding of how early trauma, due to the failures of maternal care, can continue to have an impact in adult life. 3) Bick's “psychic skin” establishes the concept in relation to infancy. The mother’s containing functions allow a first psychic skin to develop, which then defines an infant’s psychic space and affords the infant a degree of self-containment. Houzel then conceptualized this process as a stabilization of drive forces. 4) Stern's “narrative envelope” derives from the intersection between psychoanalysis and neuroscience. It gives us another way to conceptualise the development of pre-verbal communication. It may also pave the way for a finer distinction of different types of envelopes. Ultimately, in this review we find that psychic envelopes in infancy can be viewed from four different perspectives (economic, topographical, dynamic and genetic) and recommend further investigation.